Sector comercial: Desarrollo creativo e innovador de los emprendedores de la generación Z, 2023. - Siavichay Cabrera, Samuel Fernando (2024)
The objective of this research project was to analyze how creative and innovative development influences Generation Z entrepreneurs in the commercial sector. The research, descriptive in nature, employed a representative sample of 371 entrepreneurs from the city of Quevedo. Quantitative and qualitative methods were applied, including surveys, interviews, and direct observation, to collect data on the main challenges faced by entrepreneurs in technological innovation and economic benefits. The results highlighted challenges such as the insecurity that the country presents, which, according to 72.4% of those surveyed, prevents the durability of a business. Another challenge to highlight is the constant technological advancement and limited resources, as well as the notable ability to adapt to digital innovation. Likewise, this research demonstrates the promotion of Information and Communication Technologies (ICTs), which play a fundamental role in the technological innovation of Generation Z entrepreneurs. 69.80% consider ICTs to be the main basis for improving business processes and products or services to satisfy consumers, with social networks being the most used. The use of e-commerce and mobile apps is crucial to reaching a larger audience and improving experiences. Finally, creativity and innovation generate high socioeconomic benefits in the business sector, highlighting Generation Z as a group of highly creative people with an entrepreneurial spirit. It was verified that creativity is the most important engine when creating and launching a product or service to the market, as it has the capacity to provide significant value and differentiation, which can lead to consumer preference. This type of innovative product or service directly supports economic growth, generates jobs and competitiveness in the commercial sector, and promotes sustainable and environmentally responsible practices.